The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pros.23449
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage roles in the clearance of apoptotic cells and control of inflammation in the prostate gland after castration

Abstract: CD68 macrophages phagocytose apoptotic cell corpses and activate the LAP pathway, thereby contributing to the preservation of a non-inflammed microenvironment. Marked inflammation was detected when autophagy blockers were administered to castrated animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Using the cytochemical technique of Gömöri's reticulin, it was possible to observe a disorder in the stromal compartments in the prostate of the EEA group, such as disorganization of the reticular and collagen fibers. The stromal remodeling may have been caused by an increased recruitment of macrophages, especially in the stroma, where this cell type can secrete different chemical and enzymatic mediators, actively participating in tissue remodeling (Silva et al, 2018), such as extracellular matrix metalloproteinases of types 2 and 9, as observed in prostate cancer in mice (Fang et al, 2013), in altered prostate tissue of male and female gerbils (Rochel‐Maia et al, 2011) and tissue remodeling in models with hydroxyapatite grafting, or in periodontal lesions (Carneiro et al, 2009; Zambuzzi et al, 2009). According to Falleiros‐Junior et al (2016), exposure to EE during the neonatal period promotes an increase in morphological alterations, such as foci of epithelial hyperplasia associated with inflammations in the stromal and luminal compartments of the ventral prostate of adult gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…Using the cytochemical technique of Gömöri's reticulin, it was possible to observe a disorder in the stromal compartments in the prostate of the EEA group, such as disorganization of the reticular and collagen fibers. The stromal remodeling may have been caused by an increased recruitment of macrophages, especially in the stroma, where this cell type can secrete different chemical and enzymatic mediators, actively participating in tissue remodeling (Silva et al, 2018), such as extracellular matrix metalloproteinases of types 2 and 9, as observed in prostate cancer in mice (Fang et al, 2013), in altered prostate tissue of male and female gerbils (Rochel‐Maia et al, 2011) and tissue remodeling in models with hydroxyapatite grafting, or in periodontal lesions (Carneiro et al, 2009; Zambuzzi et al, 2009). According to Falleiros‐Junior et al (2016), exposure to EE during the neonatal period promotes an increase in morphological alterations, such as foci of epithelial hyperplasia associated with inflammations in the stromal and luminal compartments of the ventral prostate of adult gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the occurrence of intraepithelial macrophages in the rat prostates, tissues sectioned at 4.0 µm were submitted to immunohistochemistry for CD68, a pan‐macrophage marker 22 . Additionally, to characterize the epithelial cells in close proximity to macrophages, immunostaining to detect cellular proliferation (MCM7) and apoptosis (cleaved caspase‐3) was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages have also been shown to interact with epithelial cells in a rather complex manner, 5 secreting factors that promote mutagenic events, cellular proliferation and motility 16‐18 . In the prostate, aside from the presence of stromal and perivascular macrophages, these cells have long been reported within the epithelium after androgen withdraw induced by castration 19‐23 . These intraepithelial macrophages appear to phagocytize apoptotic epithelial cells (efferocytosis) and contribute to the remodeling of the regressing prostate 19,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, remarkable reprogramming of immune system cells (Desai et al, 2004) and smooth muscle cells (Antonioli et al, 2004(Antonioli et al, , 2007 as well as reorganization of the extracellular matrix (Vilamaior et al, 2000) have been described and associated with a redefined functional state and immune barrier system. Additionally, we have reported the occurrence of desquamation as an additional phenomenon contributing to epithelial cell deletion (Rosa-Ribeiro et al, 2014a), and a relevant role for two macrophage subpopulations in both (a) the induction of epithelial cell death (Barbosa et al, 2019) and (b) the clearance of cell corpses and maintenance of the noninflammatory status (Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%